Competing by Design / The Power of Organizational Architecture - Nadler David A; Tushman Michael L (Oxford University Press, 1997)
A Blueprint for Change, Mapping the Organizational Terrain, The Principles of Design, The Crucial Design Issues, Choosing a Basic Structure - Strategic Groups, Coordinating Work - Strategic Linking, Designing at the Enterprise Level, Designing at the Operational Level, A Process for Design, Implementing New Designs, Kowning When to Redesign, The Lessons of Design, Index.
A Blueprint for Change, Mapping the Organizational Terrain, The Principles of Design, The Crucial Design Issues, Choosing a Basic Structure - Strategic Groups, Coordinating Work - Strategic Linking, Designing at the Enterprise Level, Designing at the Operational Level, A Process for Design, Implementing New Designs, Kowning When to Redesign, The Lessons of Design, Index.